2004
DOI: 10.1038/sj.ijo.0802731
|View full text |Cite
|
Sign up to set email alerts
|

Night eating and weight change in middle-aged men and women

Abstract: OBJECTIVE:To examine the association between the habit of eating at night, and the 5-y preceding and 6-y subsequent weight changes in a middle-aged population, with particular focus on the obese. DESIGN: Prospective study with initial examination of the cohort in 1982-83, re-examination in 1987-88 and a third examination in 1992-93. SUBJECTS: The Danish MONICA cohort includes an age-and sex-stratified random sample of the population from the Western part of the Copenhagen County. Out of 2987 subjects participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 36 publications
(36 reference statements)
1
60
1
1
Order By: Relevance
“…57 These studies have found widely varying rates of nocturnal eating (from 3.8% in a community sample 36 to 55% in a bariatric surgery sample). 55 This variability is likely due to differences in sampling, means of assessment, and sample size.…”
Section: Striegel-moore Et Almentioning
confidence: 98%
“…57 These studies have found widely varying rates of nocturnal eating (from 3.8% in a community sample 36 to 55% in a bariatric surgery sample). 55 This variability is likely due to differences in sampling, means of assessment, and sample size.…”
Section: Striegel-moore Et Almentioning
confidence: 98%
“…This is in line with the results of longitudinal population studies. Andersen et al 27 reported that in a population sample of 2,111 men and women, getting up at night to eat was not associated with preceding (5 years) or subsequent (6 years) weight change, except among already obese women. This suggests that this behavior might contribute to further weight gain only in already obese women.…”
Section: Resultsmentioning
confidence: 96%
“…Night eating is associated with a defined psychiatric disorder, night-eating syndrome (nocturnal hyperphagia, insomnia, and morning anorexia). [25][26][27] This makes it less amenable to prevention and intervention in primary care. Snacking between meals is another behavior that has been associated with excessive weight.…”
Section: Specific Eating Behaviorsmentioning
confidence: 99%